2022
DOI: 10.1155/2022/8494796
|View full text |Cite|
|
Sign up to set email alerts
|

Posterior Lumbar Plexus Block Anesthesia for Elderly Patients with Lower Limb Fracture

Abstract: The incidence rate of lower limb fractures is high and has increased over the recent years, which affects the physical and mental health and the daily activities of patients. Lower limb fractures are often treated surgically. Therefore, an effective anesthesia regimen is crucial for a smooth and stable operation. To investigate the efficacy of posterior lumbar plexus block anesthesia during surgery for elderly patients with lower extremity fractures. In total, patients were divided into study and control group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Considering the diminished physiological capacity commonly observed in senior patients, the level of anesthesia needed for LMA (Laryngeal Mask Airway) may result in an inability to tolerate it, so compromising the effectiveness of the anesthetic [ 18 ]. Hence, it is crucial to implement an anesthetic protocol that achieves a harmonious equilibrium between efficient pain management and minimal physiological repercussions in this specific population [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Considering the diminished physiological capacity commonly observed in senior patients, the level of anesthesia needed for LMA (Laryngeal Mask Airway) may result in an inability to tolerate it, so compromising the effectiveness of the anesthetic [ 18 ]. Hence, it is crucial to implement an anesthetic protocol that achieves a harmonious equilibrium between efficient pain management and minimal physiological repercussions in this specific population [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%